Religious Practices of the Teuku Raja Ubiet Community Group in Gunong Kong Nagan Raya Aceh - Muchsin, Misri A.; Armi, Fadhlur Rahman (Al-Fikru: Jurnal Ilmiah, 2023)
This study aims to identify the development of religious practices and understanding of Sufism of the Teuku Raja Ubiet community group in Gunong Kong Village as an effort to reveal the veil of truth behind the claims of previous researchers. This qualitative type of research uses descriptive analysis, it is hoped that it can be known in depth the dynamics of the community in Gunong Kong Village in Sufism and faith. This research uses three data collection techniques: interview, observation, and document study. Data analysis uses data collection techniques, data reduction, presentation and conclusion drawing. The results of this research show that the beliefs of the Gunong Kong community are strongly influenced by the core teachings of Hakikat (Sufism) which have been passed down from generation to generation and used as the basis for religious tendencies. These teachings do not contradict the Shari'a because they are always guarded by charismatic authorities in Gunong Kong and Nagan Raya in general. The stereotype that the Gunong Kong community performs worship that contradicts the teachings of sharia cannot be proven.